Economic and Environmental Assessment of Plastic Waste Pyrolysis Products and Biofuels as Substitutes for Fossil-Based Fuels - Pacheco-López, Adrián; Lechtenberg, Fabian; Somoza-Tornos, Ana; Graells, Moisès; Espuña, Antonio (Frontiers in Energy Research, 2021)
The global economy is shifting toward more sustainable sources of energy. The transportation sector is a remarkable example of this fact, where biofuels have emerged as promising alternatives to traditional fossil fuels. This work presents a techno-economic and environmental assessment of existing liquid fuels in hard-to-decarbonize sectors and their emerging renewable substitutes. The comparison focuses on fossil-based, biomass-derived, and plastic waste-sourced fuel alternatives that can be used in spark-ignition (gasoline) and compression-ignition (diesel) engines. Results for diesel substitutes prove the superior performance of plastic waste pyrolysis oil in terms of production cost reduction (−25% compared to diesel) and “well-to-tank” life cycle impact reduction (−54% human health, −40% ecosystems, −98% resources). Consequently, research and development toward the conversion of plastic waste into fuels should be extended to make the technology more accessible and robust in terms of fuel quality. On the contrary, the results for gasoline alternatives are not as conclusive: bioethanol and ethanol from plastic pyrolysis have a considerably lower impact on resource scarcity than gasoline (−80% and −35% respectively) and higher on the other two life cycle endpoint categories, but they have higher production costs compared to gasoline (+57% and +130% respectively). While blends of gasoline with pyrolysis-sourced ethanol can reduce the impact on human health and ecosystems, blends with bioethanol have a lower impact on resource scarcity and increase economic profitability. This allows fuel providers to offer tradeoff solutions in the form of blends based on their priorities.